Achieving Achievements in the Economics Science Event at SMA Negeri 1 Bumiayu Through Kongsi Man - Suwarti, Sri (JUPE : Jurnal Pendidikan Mandala, 2023)
The method used is descriptive qualitative which describes how a technique for guiding students with the method is applied and how the desired results can be achieved.The implementation of KSN Economic guidance and coaching through Kongsi Man will be carried out from 2018 to November 2021. Kongsi Man can set boundaries and determine the steps that need to be taken, the resources needed to achieve them, and achievements that show progress throughout the process. The advantage of the Kongsi Man strategy for students is that they are more confident, learn to build the will to compete positively, increase experience, improve self-quality, help assess one's strengths and weaknesses and become more diligent.